Impact of local drug delivery and natural agents as new target strategies against periodontitis: new challenges for personalized therapeutic approach - Gaia Viglianisi; Simona Santonocito; Saturnino Marco Lupi; Mariacristina Amato; Gianrico Spagnuolo; Paolo Pesce; Gaetano Isola (SAGE Publishing, 2023)
Periodontitis is a persistent inflammation of the soft tissue around the teeth that affects 60% of the population in the globe. The self-maintenance of the inflammatory process can cause periodontal damage from the alveolar bone resorption to tooth loss in order to contrast the effects of periodontitis, the main therapy used is scaling and root planing (SRP). At the same time, studying the physiopathology of periodontitis has shown the possibility of using a local drug delivery system as an adjunctive therapy. Using local drug delivery devices in conjunction with SRP therapy for periodontitis is a potential tool since it increases drug efficacy and minimizes negative effects by managing drug release. This review emphasized how the use of local drug delivery agents and natural agents could be promising adjuvants for the treatment of periodontitis patients affected or not by cardiovascular disease, diabetes, and other system problems. Moreover, the review evidences the current issues and new ideas that can inspire potential later study for both basic research and clinical practice for a tailored approach.